ILLOCUTIONARY SPEECH ACTS IN THE PRESIDENTIAL SPEECH REGARDING THE RELOCATION OF THE NATIONAL CAPITAL CITY - Oktavia Surya Nur Alam (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2023)
This study aims to analyze illocutionary speech acts in speeches on the relocation of the national capital. The relocation of the national capital is a new polemic that raises pros and cons among the public. Some people consider the relocation of the capital city to have less urgency, so there is no need to do that. Leaders have an important role in convincing the public of this view. The use of language by politicians in speeches certainly has another goal, namely to convince the audience or the public. This research uses the theory of speech acts by Searle. Searle classifies illocutionary speech acts into five types. That is a declaration, assertive, expressive, directive, and commissive. The method used is the descriptive method. The results obtained from this study are that there are classifications of speech acts. That is, assertive, commissive, directive, and declarative. The results of this study indicate that these speech acts have a role in speech, one of which is to influence many people with our opinions.